The Medical Director in Integrated Clinical Care Models - Parker, Thomas F. (Clin J Am Soc Nephrol, 2015)
Integrated clinical care models, like Accountable Care Organizations and ESRD Seamless Care Organizations, present new opportunities for dialysis facility medical directors to affect changes in care that result in improved patient outcomes. Currently, there is little scholarly information on what role the medical director should play. In this opinion-based review, it is predicted that dialysis providers, the hospitals in which the medical director and staff physicians practice, and the payers with which they contract are going to insist that, as care becomes more integrated, dialysis facility medical directors participate in new ways to improve quality and decrease the costs of care. Six broad areas are proposed where dialysis unit medical directors can have the greatest effect on shifting the quality-care paradigm where integrated care models are used. The medical director will need to develop an awareness of the regional medical care delivery system, collect and analyze actionable data, determine patient outcomes to be targeted that are mutually agreed on by participating physicians and institutions, develop processes of care that result in improved patient outcomes, and lead and inform the medical staff. Three practical examples of patient-centered, quality-focused programs developed and implemented by dialysis unit medical directors and their practice partners that targeted dialysis access, modality choice, and fluid volume management are presented. Medical directors are encouraged to move beyond traditional roles and embrace responsibilities associated with integrated care.